Characterization of circular RNA expression profiles in the age-related thymic involution of Magang goose. (February 2023) - Li, Ying; Li, Bingxin; Liu, Fenfen; Yang, Lin; Wu, Qingru; Wu, Yingying; Ma, Yongjiang; Xu, Danning; Li, Yugu
Abstract: The thymus is a vital immune organ, but its function gradually declines with age. Circular RNAs (circRNAs) are related to the development of tissues and organs. In this study, bioinformatics analysis showed that 1329, 755, and 417 circRNAs were differentially expressed between the comparison groups of 6-month age (M6) and 20-embryo age (E20), 3-day post-hatch (P3), and 3-month age (M3) Magang geese, respectively. Among them, 167 circRNAs were differentially co-expressed between thymic development (E20, P3, and M3) and involution (M6). Functional analysis showed significant enrichment of phosphorylation and positive regulation of GTPase activity. Furthermore, pathway analysis has shown that glycerolipid metabolism and the Wnt signaling pathway are critical pathways in the thymic involution process. Finally, we constructed the competitive endogenous RNA (ceRNA) network. The results of this study suggest that circRNAs may be involved in the age-related thymic involution of the Magang goose. Highlights: This study identified the profiles of circRNAs in the goose thymus for the first time. 83805 circRNAs were detected in the thymus of Magang geese. There were 1329, 755, and 417 DEcircRNAs in different stages of thymic involution in Magang geese. circRNA may regulate the thymic involution in Magang goose through the ceRNA network.